Imaging in neurological and vascular brain diseases (SPECT and SPECT/CT) - Lucena, Filipa (2015)
Since the first in vivo studies of cerebral function with radionuclides by Ingvar and Lassen, nuclear medicine (NM) brain applications have evolved dramatically, with marked improvements in both methods and tracers. Consequently it is now possible to assess not only cerebral blood flow and energy metabolism but also neurotransmission. Planar functional imaging was soon substituted by single-photon emission computed tomography (SPECT) and positron emission tomography (PET); it now has limited application in brain imaging, being reserved for the assessment of brain death.